Preservation of facial nerve functions during vestibular schwannoma surgery: outcome analysis - Ashraf Mohamed Farid; Ahmed Rizk Elkholy (Egyptian Journal of Neurosurgery, 2019)
Abstract Background The goal of modern vestibular schwannoma surgery is not only to complete tumor removal but also to preserve functions. Cerebellopontine angle surgery carries a significant risk of impairing facial nerve function especially with large masses. Avoidance of facial nerve injury postoperatively requires preoperative and intraoperative identification and hence the role of preoperative imaging and intraoperative monitoring. Objectives To evaluate the impact of identification of facial nerve preoperatively and intraoperative neurophysiological monitoring on the preservation of facial nerve function. Study design This is a retrospective clinical case series. Patients and methods This study was conducted on 32 patients operated upon for excision of vestibular schwannoma. All had hearing loss but intact facial nerve (House-Brackmann (HB) grade I). Fast imaging employing steady-state acquisition was used preoperatively to predict the location of the facial nerve. Intraoperative monitoring was used for all patients. Patients were followed up for 24 months. Results House-Brackmann grade I was achieved in 68.75% of patients. Grade VI was achieved in 12.5% of patients. Near-total removal was achieved in 62.5% of patients, and subtotal removal was achieved in 37.5%. The higher percentage of normal facial function postoperatively (HB grade I) was associated with subtotal resection and soft consistency of the neoplasm. Conclusion Facial preservation requires preoperative prediction of the location of the nerve in relation to the capsule, extra-arachnoidal dissection during surgery, and subtotal resection if intraoperative monitoring predicts a high risk.